Study of n/γ discrimination using 3He proportional chamber in high gamma-ray fields - Joonbum Choi; Junesic Park; Jaebum Son; Yong Kyun Kim (Nuclear Engineering and Technology, 2019)
The 3He proportional chamber is widely used for neutron measurement owing to its high neutron detection efficiency and simplicity for gamma-ray rejection. In general, the neutron and gamma-ray signals obtained from the 3He proportional chamber can be easily separated by the difference in the pulse heights. However, for a high gamma-ray field, the gamma-ray signal cannot be precisely eliminated by the pulse height due to gamma-ray pulse pileup which causes the pulse height of gamma-ray pulse to increase and making the pulses due to neutrons and gamma rays indistinguishable. In this study, an improved algorithm for n/γ discrimination using a parameter, which is the ratio of the rise time to the pulse height, is proposed. The n/γ discrimination performance of the algorithm is evaluated by applying it to 252Cf neutron signal separation from various gamma-ray exposure rate levels ranging 0.1–5 R/h. The performance is compared to that of the conventional pulse-height analysis method in terms of the gamma elimination ratio. The suggested algorithm shows better performance than the conventional one by 1.7% (at 0.1 R/h) to 70% (at 5 R/h) for gamma elimination. Keywords: 3He proportional chamber, Neutron detector, n/γ discrimination, Algorithm, High gamma-ray field